Cognitive enhancement kept within contexts: neuroethics and informed public policy - Shook, John R.; Galvagni, Lucia; Giordano, James (Frontiers in Systems Neuroscience, 2014)
Neuroethics has greater responsibilities than merely noting potential human enhancements ascribed to brain science, and tracking their implications for ethics and civic life. Neuroethics must utilize current neuroscientific knowledge to shape incisive discussions about what could count as enhancement in the first place, and what should count as genuinely ‘cognitive’ enhancement. Where cognitive processing and mental life are concerned, the lived context of psychological performance is paramount. Starting with an enhancement to the mental abilities of an individual, only performances on real-world exercises can determine what is actually cognitively improved. And, what concretely counts as some specific sort of cognitive improvement is largely determined by classificatory frameworks of cultures, not brain scans or laboratory experiments. As well, the public must ultimately evaluate and judge the worthiness of individual performance enhancements; we mustn’t presume that public approval towards enhancers will automatically arrive without due regard to civic ideals such as the common good or social justice. In the absence of a nuanced appreciation for the control which performance and public contexts exert over what ‘cognitive’ enhancements could actually be, enthusiastic promoters of cognitive enhancement can too easily depict safe and effective brain modifications as good for society. These enthusiasts are not unaware of hurdles for reliable enhancement through neurophysiological modifications. Yet those observations are far more common than penetrating investigations into the implications of such hurdles for both sound public understanding of cognitive enhancement, and development of policy to guide cognitive enhancement. In this essay, we seek to more accurately define and contextualize cognitive performance enhancement, and offer recommendations to ensure that cognitive enhancers that truly deserve public approval can be better identified and developed.